Nonautonomous linear Hamiltonian systems : oscillation, spectral theory and control /: oscillation, spectral theory and control. ([2016]) - Johnson, R (Russell); Obaya, Rafael; Novo, Sylvia; Núñez, Carmen; Fabbri, Roberta
No abstract available